A Challenging Case of Congenital Diaphragmatic Hernia Managed Successfully: A Case Report - Saurabh Jitendra Tiwari; Apoorva Kulkarni; Geeta Kekre; Abhaya Gupta; Shalika Jayaswal; Paras Kothari (EL-Med-Pub, 2020)
Despite advances in antenatal diagnosis and perinatal care, mortality rate remains elevated in patients with congenital diaphragmatic hernia (CDH). We report a case of left sided CDH in a term baby with persistent gastroesophageal reflux (GER) after repair, and persistent pulmonary hypertension requiring multiple vasodilators. Baby required high frequency oscillatory ventilation for 6 weeks. After failed medical management, bedside gastrostomy in neonatal intensive care unit was done. Nissen's fundoplication was done later. After 2.5 months child was discharged asymptomatically.